2021
DOI: 10.1080/13602381.2021.1905410
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the talent management mechanism and self-perceived talent status on work engagement: the case of Japan

Abstract: This study uses a quantitative analysis to investigate the connection between the talent management (TM) mechanism and work engagement with a perceived moderating effect of the self-perceived talent status on work engagement. Using responses from 471 respondents in six Japanese firms, I propose and test hypotheses regarding the TM mechanism, work engagement and the moderating role of the self-perceived talent status between the TM mechanism and work engagement. The results demonstrate that the TM mechanism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…Transformational leadership is negatively related to work engagement. This deviates with the findings of Church (2013), Sopiah et al (2020), Toka and Hamida (2020) and Ishayama (2021).…”
Section: Discussion Of the Findingscontrasting
confidence: 95%
See 1 more Smart Citation
“…Transformational leadership is negatively related to work engagement. This deviates with the findings of Church (2013), Sopiah et al (2020), Toka and Hamida (2020) and Ishayama (2021).…”
Section: Discussion Of the Findingscontrasting
confidence: 95%
“…There is a significant positive relationship between talent management and work engagement (Toka & Hamida, 2020). Ishayama (2021) found that talent management has an impact on work engagement.…”
Section: Talent Management and Work Engagementmentioning
confidence: 99%
“…Barkhuizen et al [28] discovered that work engagement can be positively influenced by the talent management mechanism. Among the factors that contribute to work engagement, talent management plays an important role [29]. Consequently, this study suggests that talent management has a positive impact on employees' work engagement.…”
Section: Work Engagementmentioning
confidence: 78%
“…Training is defined as the extent to which the HR department designs training program to enhance employee skills and knowledge, which in turn help in career advancement and achieving high-performance work (Armstrong et al, 2021;Garavan et al, 2021;Park et al, 2022). Prior studies have confirmed the significant impact of HR training on employee work engagement during crises such as pandemic (Armstrong et al, 2021;Azizi et al, 2021;Garavan et al, 2021;Gim et al, 2021;Ishiyama, 2021;Risley, 2020). Therefore, the following hypotheses are proposed: H1.…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%